Implementasi Low Power Multi Sensor Node pada Wireless Sensor Network - Muhammad Fatikh Hidayat; Barlian Henryranu Prasetio; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The power source is one of the important things that have to be noticed at the application of WSN on wide area scope, data transmission and monitoring scope of sensor module that used by sensor node cause high amounts of sensor node required. Especially if the node only use to monitor a type of environmental condition, while the monitoring needs are required to be able to monitor many type of condition, on those case more amounts and also power sources needed according to the area and the type of environmental condition to be monitored by sensor nodes. To be able to solve the problem, the authors implement a sensor node equipped with multi sensors and including a low power mechanism that is useful to determine when the sensor node will activating sleep mode or not. The sensor node is designed using ATmega328P as microcontroller with NRF24L01 as wireless communication module, equipped RTC module as time data source which use as time stamp of running system. With the low power mechanism inside the sensor nodes reduces current consumption up to 65,3%, so as to extend the active life of the sensor node compared with the absences of the low power mechanism.